Combination of anlotinib with immunotherapy enhanced both anti-angiogenesis and immune response in high-grade serous ovarian cancer - Lan, Hongwei; Liu, Hui; Hou, Helei; Zhang, Chuantao; Zhu, Jingjuan; Zhou, Na; Zhang, Xiaochun (Frontiers in Immunology, 2025)
BackgroundHigh-grade serous ovarian cancer (HGSOC) poses significant treatment challenges due to frequent recurrence and resistance to conventional therapies. Combination of anlotinib with immunotherapy have showed promise in various cancers, but its impact on HGSOC remains to be fully elucidated.MethodsA retrospective analysis was performed on 36 HGSOC patients treated with anlotinib-based therapies, including both monotherapy and combination treatment with anti-PD-L1/anti-PD-1 antibody (aPD-L1/aPD-1). Peripheral blood mononuclear cell-derived patient-derived xenograft (PBMC-PDX) model was established from drug-resistant recurrent HGSOC patient-derived tumor cells, and single-cell RNA sequencing (scRNA-seq) was conducted to dissect the TME following treatment with anlotinib, anlotinib + aPD-L1 and anlotinib + aPD-1.ResultsClinical analysis revealed a disease control rate (DCR) of 71.43% for anlotinib monotherapy, which improved to 100% when combined with aPD-L1/aPD-1. In PBMC-PDX models, treatment evaluation showed that anlotinib decreased tumor volume, an effect further enhanced by its combination with aPD-L1. scRNA-seq analysis demonstrated that anlotinib reduced the proportions of myofibroblastic cancer-associated fibroblasts and ESM1+ endothelial cells, resulting in decreased angiogenesis. The combination of anlotinib and aPD-L1 further amplified these effects, promoting CD8+ T cell infiltration and reversing T cell exhaustion, whereas anlotinib + aPD-1 showed limited efficacy in this regard. Additionally, anlotinib + immunotherapy induced a shift toward M1 polarization of myeloid cells, enhanced anti-tumor activity, and inhibited immune escape. Cell-cell communication analysis revealed reduced APP-CD74 signaling and increased CD99-CD99 signaling, which might contribute to immune activation.ConclusionThe combination of anlotinib and aPD-L1 effectively modulates the HGSOC tumor microenvironment by inhibiting angiogenesis, enhancing immune infiltration, and reversing T cell exhaustion.